Pengembangan Pembelajaran Kemahiran Berbicara Bahasa Arab Menggunakan Pendekatan Cross Cultural Understanding - Cahya Edi Setyawan (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2017)
Language and culture are the two components that can not be separated from human communication. As a tool to communicate with one and another, many discussion about the theory between language and culture. The relationship between the language and culture of linguists is the most common concern for those who have included language instruction for foreign language, understanding the language where different cultural complexities are needed in this study were a concern of the Arabic language. Moreover, many scholars emphasize the learning model of Arabic-speaking skills on the basis of theory through cultural understanding. The main aspect you should be interested in learning the Arabic language such as cross cultural knowledge, cross cultural awareness, cross-cultural sensitivity, cross cultural. The theory of Odes developing the intentional skill of speaking Arabic, devolution of educational materials, the development of professional teacher, the development of approaches and the development of the method, and the development of learning assessment. Each component had elements of mutual cultural understanding.